Politecnico di Torino POP Report 2024 - Lisa Giovanetto; Giulia Lerda; Simone Bertin; Keem Justin Adorable (European Journal of Volunteering and Community-Based Projects)
The POP Financial Report for Politecnico di Torino aims to provide a comprehensive framework detailing the university’s achievements, future directions, and alignment with both national and global priorities. It includes a detailed look at demographics, highlighting student diversity, enrollment trends, and demographic shifts that impact the university’s strategic goals. In rankings, the POP showcases the Politecnico’s standing among Europe’s leading technical universities, demonstrating its strengths in areas such as engineering and architecture.